The relative importance of information items and preferred mode of delivery when disseminating results from trials to participants: A mixed‐methods study - Jessica Wood; Seonaidh C. Cotton; Katie Gillies (Wiley, 2022)
Abstract Background Participants want to receive the results of trials that they have participated in. Dissemination practices are disparate, and there is limited guidance available on what information to provide to participants and how to deliver it. Objectives This study aimed to establish what trial participants believe should be included in a results summary and how this information should be delivered. Methods A mixed‐methods design was used with focus groups and interviews involving women convenience‐sampled from two host randomized‐controlled trials. Participants ranked information items in order of their importance for inclusion in a trial results summary and potential modes of delivery by preference. All participants provided written informed consent. Results Sixteen women (mean age [SD] = 71.6 [9.7] years) participated. Participants ranked 'individual results from the study' and 'summary of overall trial results' as most important. Themes such as reassurance and setting results in context were identified as contributing to participants' decisions around ranking. 'A thank you for your contribution to the study' was ranked the least important. Delivery by post was the preferred mode of receiving results, with receiving a hard copy of results cited as helpful to refer back to. Conclusion Our findings provide insight into what information trial participants deem as important when receiving trial results and how they would like results delivered. Involving patients during development of trial results to be communicated to participants could help to ensure that the right information is delivered in the right way. Patient or Public Contribution Public partners were involved in focussed aspects of study conduct.